Centralizing over-the-counter markets? - Jason Allen; Milena Wittwer (Bank of Canada, 2021)
We identify a sizable wealth redistribution channel which creates a monetary policy trade-off whereby short-term economic stimulus is followed by persistently lower output over the medium term. This trade-off is stronger in economies with more nominal household debt but weakened by a more aggressive monetary policy stance and under price-level targeting. Given this trade-off, low-for-long episodes can lead to persistently depressed output. The mediumterm implications of the wealth redistribution channel rely on the presence of labor supply heterogeneity, which we show both analytically and in the context of an estimated New Keynesian general equilibrium model with household heterogeneity.In traditional over-the-counter (OTC) markets, investors trade bilaterally through intermediaries referred to as dealers. An important regulatory question is whether to centralize OTC markets by shifting trades onto centralized platforms. We address this question in the context of the liquid Canadian government bond market. We document that dealers charge markups even in this market and show that there is a price gap between large investors who have access to a centralized platform and small investors who do not. We specify a model to quantify how much of this price gap is due to platform access and assess welfare effects. The model predicts that not all investors would use the platform even if platform access were universal. Nevertheless, the price gap would close by 32%-47%. Welfare would increase by 9%-30% because more trades are conducted by dealers who have high values to trade.
Keywords: D40; D47; G10; G20; L10; 330; Financial institutions; Market structure and pricing